Perancangan Interaksi dan Antarmuka Pengguna Sistem Informasi Inventaris Aset pada Divisi IT Quality Assurance PT. Telekomunikasi Selular - Fitria Handayani; Retno Indah Rokhmawati; Diah Priharsari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
PT. Telekomunikasi Selular is one of the cellular telecommunications operator companies in Indonesia. Telkomsel has tools which help manage all business activities, one of which is the ITQA Asset Inventory Information System. It will be developed to assist the operations of the IT Quality Assurance division; specifically, in the IT Strategy and Tools department in managing asset inventory which over time increases in quantity so that it makes management more difficult; besides, the managers think that they need tools to be more orderly in the administrative process. Therefore, it is necessary to design an interaction and user interface which can solve the problems that have been described. Furthermore, this design used Design Thinking with five stages, which were empathize, define, ideate, prototype, and test. The design of the interaction and user interface for system was a high-fidelity prototype for the three user segments that are ITQA, requestor and administrator. Then, each system was evaluated by using usability testing which produced qualitative data in the form of feedback from users who overall state that the system was good and easy. Moreover, the ITQA Asset Inventory Information System for requestor was also evaluated by using the EUCS (End-User Computing Satisfaction) questionnaire which resulted in 49.58% of 16 respondents who agree and 35.64% of 16 respondents who strongly that the ITQA Asset Inventory Information System is satisfying in terms of content, accuracy, format, ease of use and timeliness.